What causes acute coronary syndromes? Applying Koch's postulates. - Monaco, C; Mathur, A; Martin, J (2005)
The term "acute coronary syndromes" (ACS) is used to describe a heterogeneous spectrum of clinical conditions. This includes myocardial infarction, non-ST-elevation myocardial infarction, and unstable angina. These conditions are linked by a similar constellation of signs and symptoms but not necessarily by a common pathophysiology. They are syndromes. Several different hypotheses exist that have attempted to explain the pathological mechanisms that are involved in these conditions, however, it is not clear whether ACS are caused by variations of a single disease process or by several disease processes. The contribution of both vessel wall- and blood-related factors in the pathogenesis of acute coronary syndromes is herein discussed with the guidance of Koch's postulates.